Evaluación de compost inoculado con microorganismos eficientes autóctonos sobre la producción de especies hortícolas en huertos orgánicos - Gallo Encarnación, Angie Abigail (2023)
The objective of this work was to evaluate the influence of eco-functional compost on the production of horticultural species in an organic garden established in a community in Bolívar-Manabí canton. The research was developed in two phases: the first phase involved laboratory work for the preparation of the inoculum with bacterial strains (Bacillus. Cereus and B. subtilis,) and fungal (Trichoderma. longibrachiatum), which were inoculated in the composting of the mixture of agricultural waste: peanut shell and bovinaza, using the Indore method (with and without inoculation of efficient microorganisms), during the process the physical characteristics (temperature, pH, electrical conductivity, humidity), chemical (macro and micronutrients), microbiological (aerobic mesophils,fecal coliforms and Staphylococci) and phytotoxic (Seed Germination Index) were evaluated in the compost. The Biopreparation with the inoculums was obtained from the Ceparium that exists in the Molecular Biology Laboratory at ESPAM MFL. The results obtained in the composting indicate that the best quality compost was achieved in the batteries inoculated with microorganisms, since it meets the largest number of physical, chemical and microbiological parameters, according to production standards of organic fertilizers. In the second phase, the beneficial effect of compost inoculated with MS on the development and production of cultivated horticultural plants was verified, finding significant differences in most of the variables evaluated, compared to the orchard where compost without inoculations was used as substrate.